LENDIR BEKICOT MENINGKATKAN JUMLAH SEL MAKROFAG PADA PENYEMBUHAN LUKA PASCA PENCABUTAN GIGI MARMUT - Dewi, Putu Sulistiawati; DS, Setiawan (Faculty of Dentistry, Mahasaraswati Denpasar University, 2020)
Tooth extraction is a common practice in dentistry. Tooth extraction will cause injuries that need healing before they can return to the physiological state of the oral cavity. Snail mucus contains beta agglutinin (antibodies) in plasma (serum), achasin protein, glycoconjugate and sulfate levels which can accelerate wound healing by increasing the mobilization of macrophage cells on day 5 after tooth extraction. The purpose of this study was to determine the effectiveness of snail mucus on the number of macrophage cells in wound healing after extraction of guinea pigs. The research method used was pure experimental research using 32 guinea pigs as samples. Guinea pigs were divided into 2 (two) groups: the control group was given 2% CMC-Na gel and the treatment group was given snail mucus after having been extracted. Calculation of the number of macrophages is done on the 5th day. The results showed the mean number of macrophage cells in the control group was 13.06 cells, and the treatment group was 17.44 cells. After being analyzed using the Independent t-test with significance Ï <0.05, it was found that there were significant differences in the number of macrophage cells in the test group and the control group. From this study it can be concluded that snail mucus is effective in increasing the number of macrophage cells in the process of wound healing after tooth extraction. Keywords : snail mucus, macrophage cell, tooth extraction